Comparative study of irradiation effects in graphite and graphene induced by swift heavy ions and highly charged ions. (April 2016) - Zeng, J.; Liu, J.; Yao, H.J.; Zhai, P.F.; Zhang, S.X.; Guo, H.; Hu, P.P.; Duan, J.L.; Mo, D.; Hou, M.D.; Sun, Y.M.
Abstract: Highly oriented pyrolytic graphite (HOPG) and monolayer graphene were irradiated by swift heavy ions (SHI, 479 MeV 86 Kr and 250 MeV 112 Sn) and highly charged ions (HCI, 4 MeV 86 Kr 19+ ). The irradiation effects caused by different types of irradiation were investigated by Raman spectroscopy. It was found that the intensity ratio of D peak to G peak ( I D /I G ) in the case of HCI was higher than that of SHI for the same ion fluence in HOPG. The larger I D /I G indicates that synergistic effects of kinetic and potential energies of medium energy HCI has to be considered during the energy deposition process. A turning point was detected during the evolution process of I D / I G with fluence obtained from SHI and HCI impacted graphene, while such turning point was absent in the case of HOPG. The Lucchese's phenomenological model was modified and the experimental data of I D / I G vs. fluence for HOPG and graphene was completely following the modified model. According to this model, energetic ions induced both structurally disordered and activated regions in graphene. The competing mechanism of these two regions resulted in three different trends of the I D /I G variation in the case of graphene whereas in HOPG, such mechanism was not observed.